ANALISIS PENGARUH PEMAHAMAN KONSEP TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA MATERI TEOREMA PYTHAGORAS - Hulaima; Cahya Mar'a Saliha Sumantri (Center of Education Journal (CEJou), 2024)
This study aims to describe how the influence of conceptual understanding on the problem solving abilities of class VIII students at MTs Negeri 6 Pasuruan, on the Pythagorean theorem material. This study used a descriptive qualitative method with 3 research sample, which were selected using a purposive sampling technique. The research instrument used was a conceptual understanding questionnaire which contained 5 descriptive questions and 5 statements with correct, doubtful and false answer choices to determine the research sample. Then a problem solving test according to the Polya problem solving steps as many as 2 description questions. The results of the study showed that students with high conceptual understanding had good problem solving abilities and did not experience difficulties and did problem solving according to Polya’s steps. Students with moderate understanding of concepts have good abilities but experience difficulties in solving problems and according to Polya steps. Whereas students with low conceptual understanding have poor problem-solving abilities, so they experience difficulties and do not solve problems according to Polya’s steps.